2015
DOI: 10.1371/journal.pgen.1005239
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of DNA-PK Signaling and T-Cell Differentiation by Targeted Genome Editing in a prkdc Deficient iPSC Disease Model

Abstract: In vitro disease modeling based on induced pluripotent stem cells (iPSCs) provides a powerful system to study cellular pathophysiology, especially in combination with targeted genome editing and protocols to differentiate iPSCs into affected cell types. In this study, we established zinc-finger nuclease-mediated genome editing in primary fibroblasts and iPSCs generated from a mouse model for radiosensitive severe combined immunodeficiency (RS-SCID), a rare disorder characterized by cellular sensitivity to radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 68 publications
(97 reference statements)
0
19
0
Order By: Relevance
“…Once the expression of TALEN monomers in HEK293T cells was confirmed (EV1B), we established proof of principle for gene editing in FA-A MEFs. Using a stepwise experimental approach as followed in previous gene-targeting studies (Bednarski et al, 2016;Diez et al, 2017;Rahman et al, 2015), we observed relatively high transfection efficiencies (mean value of 30%) and viabilities (ranging from 47% to 78%), indicating that in this cell type cytotoxicity was not a limiting factor to perform gene editing. We also observed that when a donor template was used together with the TALENs, the percentage of repair by NHEJ was significantly reduced; suggesting that a proportion of NHEJ repair was replaced by HDR in the presence of a donor template.…”
Section: Discussionmentioning
confidence: 55%
“…Once the expression of TALEN monomers in HEK293T cells was confirmed (EV1B), we established proof of principle for gene editing in FA-A MEFs. Using a stepwise experimental approach as followed in previous gene-targeting studies (Bednarski et al, 2016;Diez et al, 2017;Rahman et al, 2015), we observed relatively high transfection efficiencies (mean value of 30%) and viabilities (ranging from 47% to 78%), indicating that in this cell type cytotoxicity was not a limiting factor to perform gene editing. We also observed that when a donor template was used together with the TALENs, the percentage of repair by NHEJ was significantly reduced; suggesting that a proportion of NHEJ repair was replaced by HDR in the presence of a donor template.…”
Section: Discussionmentioning
confidence: 55%
“…1b), we established proof of principle for gene editing in FA-A MEFs. Using a stepwise experimental approach as followed in previous gene-targeting studies 25,68,69 , we observed relatively high transfection efficiencies (mean value of 30%) and viabilities (ranging from 47% to 78%), indicating that in this cell type cytotoxicity was not a limiting factor to perform gene editing. We also observed that when a donor template was used together with the TALENs, the percentage of repair by NHEJ was significantly reduced; suggesting that a proportion of NHEJ repair was replaced by HDR in the presence of a donor template.…”
Section: Discussionmentioning
confidence: 76%
“… 57 Gene-editing tools have also been developed to correct gene mutations associated with ADA-SCID 258 and radiosensitive SCID, caused by impaired DNA-dependent protein kinase (DNA-PK) activity. 259 Thus, the ability to efficiently alter gene sequences in T cells, CD34+ HSCs, and human pluripotent cells can provide therapeutic gene-editing strategies for a broad range of different human immunodeficiencies.…”
Section: Gene Therapy Applicationsmentioning
confidence: 99%